Disease Patterns of Ankylosing Spondylitis Associated Treatment Patterns and Drug Utilization among Affected Patients: Disease Patterns of Ankylosing Spondylitis - Rashid, Muhammad Umer; Khurshid, Amina; Shaukat, Hassan; Ashraf, Fahd Farooq; Lodhi, Muhammad Haseeb; Naveed, Amir; Habib, Muhammad Farrukh (Pakistan Journal of Health Sciences, 2024)
Ankylosing Spondylitis is disease with significant morbidity. With biological DMARDs, treatment is revolutionized compared to conventional options. The article will discuss disease pattern, risk factors and treatment response of various drugs on this disease. Objective: To evaluate the prevalence, risk factors, treatment patterns, and drug utilization associated with Ankylosing Spondylitis (AS) among patients in clinical practice. Methods: This cohort study was done at territory care hospital in Rawalpindi from June 23 to December 23. Data comprised of methods to identify AS, particular tests used to verify diagnosis, numerical and clinical traits of patients included. Study also peruse percentage of patients identified as HLA-B27 positive, Time elapsed between initial symptom appearance and clinical diagnosis of AS, satisfaction of classification criteria and treatment strategies employed, such as advanced therapies for controlling AS disease activity. Results: Mean values for current disease occurrences and functional index outcomes were 3.3 ± 2.1 and 1.8 ± 1.09 in the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Bath Ankylosing Spondylitis Functional Index (BASFI) were used, respectively. Patients in study received treatment with adalimumab (43%) and Infliximab (27%) for an average period of 3.1 ± 2.1 years. Treatment satisfaction showed convenience domain had lowest score (4.2), whereas scores for side effects, effectiveness, and global satisfaction were 93.7, 75.41, and 73.81, respectively. Conclusions: Among bDMARDS adalimumab was most administered followed by Infliximab. Better therapeutics have improved patient satisfaction. Research revealed a significant decrease in productivity as a result of AS